Insights Into Unveiling a Potential Role of Tertiary Lymphoid Structures in Metastasis - Mustapha, Rami; Ng, Kenrick; Monypenny, James; Ng, Tony (Frontiers in Molecular Biosciences, 2021)
Tertiary lymphoid structures (TLS) develop in non-lymphatic tissue in chronic inflammation and cancer. TLS can mature to lymph node (LN) like structures with germinal centers and associated vasculature. TLS neogenesis in cancer is highly varied and tissue dependent. The role of TLS in adaptive antitumor immunity is of great interest. However, data also shows that TLS can play a role in cancer metastasis. The importance of lymphatics in cancer distant metastasis is clear yet the precise detail of how various immunosurveillance mechanisms interplay within TLS and/or draining LN is still under investigation. As part of the tumor lymphatics, TLS vasculature can provide alternative routes for the establishment of the pre-metastatic niche and cancer dissemination. The nature of the cytokine and chemokine signature at the heart of TLS induction can be key in determining the success of antitumor immunity or in promoting cancer invasiveness. Understanding the biochemical and biomechanical factors underlying TLS formation and the resulting impact on the primary tumor will be key in deciphering cancer metastasis and in the development of the next generation of cancer immunotherapeutics.